Bayesian analysis of parental intentions to promote physical activity in young people with cerebral palsy - Ruiz, Alfredo; Finni, Taija; Rintala, Pauli; Kaseva, Kaisa; Ng, Kwok (European Federation of Adapted Physical Activity, 2026)
This study investigates the determinants of parents’ intentions to support physical activity in their children with cerebral palsy (CP), guided by the Theory of Planned Behavior (TPB). It is hypothesized that parental intention to support PA in young people with CP will be influenced by attitude, subjective norms, and perceived behavioural control. Sixteen parents of young people with CP participating in the Exercises for CP (EXECP) intervention, were surveyed using a questionnaire developed based on the TPB constructs: Attitude, subjective norms, perceived behavioural control, and intention. Data was collected prior to the 3-month EXECP intervention, after the participants had already familiarized themselves with study procedures. A Bayesian statistical approach was central to the study´s methodology, employing Bayesian regression analysis, Bayesian correlation and model comparison tests, to evaluate the determinants of parental intentions to support physical activity in their young people with CP. The results showed that perceived behavioural control is the predominant factor influencing parental intentions, overshadowing attitude, and subjective norms. This finding underscores the crucial role of parents' perceived capabilities in facilitating physical activity in young people with CP. These insights highlight the need for interventions that strengthen parental efficacy and provide accessible resources, focusing on tailored, parent-centric strategies. Emphasizing perceived behavioural control as a crucial factor, the findings suggest pathways for interventions that empower parents with the knowledge and resources to facilitate physical activity in their children with CP.